Smart car with security camera for homeland security - Poonsak Sirichai; Somkuan Kaviya; Preecha P. Yupapin (My University, 2010)
We present a new design of safety car system for car accidence investigation and homeland security. Radio receiver and security camera are imposed to involve in the car manufacturing, which can be used for car accidence and crime suspect investigations, and navigation. Moreover, the road situation and the available route can also be reported, which is available for road traffic managements. In case of the security camera is in operation, the investigation data can be kept in the secret until the investigation is taken place by the authorized party, which is required for the fair judgment and investigation of both parties. Furthermore, the crime suspect investigation and alarming can also be implemented into the system for crime prevention, which is useful for homeland security applications.
Keywords: Suspect; Homeland; Security system; Accident investigation; Trade Secret Protection Methods